The Psychology of Generation Z Investors: Mental Accounting, Loss Aversion, and Gender Dynamics in Greater Bandung - Fauji, Ifan; Simatupang, Frido Saritua (International Journal of Management Science and Information Technology, 2026)
The growth of young investors supported by digital technology has not always been followed by the quality of completely rational investment decisions. This study aims to analyze the influence of mental accounting and loss aversion on Generation Z's investment decisions in the Greater Bandung area and test gender as a moderation variable. The research uses a quantitative approach with a cross-sectional survey design. Data was obtained through questionnaires from 115 Generation Z respondents who are domiciled in Greater Bandung and have investment experience. Samples were selected based on research criteria, while analysis was conducted using descriptive statistics, multiple linear regression, and Moderated Regression Analysis with IBM SPSS Statistics 25. The results show that mental accounting has a negative and significant effect on investment decisions. Loss aversion is negative but not significant, while the interactions of mental accounting with gender and loss aversion with gender are also not significant. The model explains 52.1% of the variance in investment decisions (Adjusted R² = 0.521). Theoretically, the findings indicate that cognitive and emotional biases do not exert equal explanatory power in Generation Z investment decisions and that gender does not necessarily condition these relationships. Practically, the results support portfolio-level evaluation tools and behavioral-finance education that help young investors distinguish useful fund discipline from rigid mental accounting.
Keywords: Mental accounting; Loss aversion; Investment decisions; Generation Z; Gender